Renal Function Salvage After Delayed Endovascular Revascularization of Acute Renal Artery Occlusion in Patients With Fenestrated-Branched Endovascular Aneurysm Repair or Visceral Debranching. (August 2018) - Heidemann, Franziska; Kölbel, Tilo; Debus, E. Sebastian; Diener, Holger; Carpenter, Sebastian W.; Rohlffs, Fiona; Tsilimparis, Nikolaos
Purpose: To analyze the renal function and outcome after delayed (>6 hours) endovascular revascularization of acute renal artery occlusion (RAO) in patients with fenestrated-branched endovascular aneurysm repairs (EVARs) or open visceral debranching.Methods: A single-center retrospective analysis was conducted involving 7 patients (mean age 61 years, range 49–72; 5 women) with 9 RAOs treated with endovascular revascularization between December 2014 and March 2017. Three patients had a solitary kidney with chronic renal insufficiency; 1 patient had bilateral occlusions as the acute event. Initial aortic surgery included 5 branched and 1 fenestrated EVAR as well as 1 open visceral debranching operation. Revascularization of the RAO was performed using aspiration thrombectomy, local lysis therapy, and stent-graft relining. The median time between initial aortic surgery and RAO was 10 months (range 0.5–17).Results: Median renal ischemic time to revascularization was 24 hours (range 7–168). Technical success was 100%, with 1 procedure-related access complication. Temporary dialysis dependency occurred in 4 patients. Mean in-hospital stay was 17 days (range 7–32) with 1 postoperative death at day 10 due to cardiac arrest of unknown cause. Mean follow-up was 10.3 months (range 1.5–27) in 5 of 6 discharged patients. During follow-up, 1 reintervention for recurrent occlusion was performed. At follow-up imaging, all renal arteries were patent. No permanent dialysis dependency occurred.Conclusion: Renal function can be salvaged by delayed revascularization for RAO with prolonged renal ischemia. The endovascular approach with aspiration thrombectomy, local lysis, and stent-graft relining is a feasible technique for revascularization after RAO in patients with fenestrated-branched EVAR or open visceral debranching.